Urbanistic and Rustic Artistic Space and Its Realization in Modern Ukrainian Literature - Мариняк, Руслана (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article analyses characteristic features of the urbanistic and rustic types of artistic space, points out the differences observed in defining the categories chronotope, locus, topos and, actually, artistic space. Subject-thematic dominants that determine the functions of the urban and rural spaces realized in modern fiction are studied. An analysis of the artistic structuring of the loci town-village is conducted. It is proved that the individuality of the artistic realization of the urban and rustic space depends on the author’s existence, which is influenced by the emotional-psychological state of the author, his former life and creative experience, attributive and odd characteristics.